2020
DOI: 10.3390/biology9120457
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis of Eosinophil Granulocytes

Abstract: In the past 10 years, the number of people in the Czech Republic with allergies has doubled to over three million. Allergic pollen catarrh, constitutional dermatitis and asthma are the allergic disorders most often diagnosed. Genuine food allergies today affect 6–8% of nursing infants, 3–5% of small children, and 2–4% of adults. These disorders are connected with eosinophil granulocytes and their apoptosis. Eosinophil granulocytes are postmitotic leukocytes containing a number of histotoxic substances that con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 124 publications
0
2
0
Order By: Relevance
“…An increased number of granulocytes may cause various allergic diseases in patients. This phenomenon may help us to reveal the adverse reactions caused by PH applied in clinics, such as anaphylaxis, which has been reported to be related to anomalous level of granulocytes [45]. These issues need further investigation not only in animal experiments, but also in clinical trials.…”
Section: Discussionmentioning
confidence: 94%
“…An increased number of granulocytes may cause various allergic diseases in patients. This phenomenon may help us to reveal the adverse reactions caused by PH applied in clinics, such as anaphylaxis, which has been reported to be related to anomalous level of granulocytes [45]. These issues need further investigation not only in animal experiments, but also in clinical trials.…”
Section: Discussionmentioning
confidence: 94%
“…However, in vitro studies have demonstrated that their survival can be extended up to 14 days following cytokine stimulation. The dominant population of eosinophils comprises gastrointestinal eosinophils residing in the lamina propria in all segments of the gastrointestinal tract below the esophagus [12][13][14][15]. The primary function of eosinophils is protection against multicellular parasites, which is achieved through the presence of specific acidophilic granules in the cytoplasm comprising, among others, MBP, ECP, eosinophil peroxidase (EPO), and eosinophil-derived neurotoxin (EDN).…”
Section: Discussionmentioning
confidence: 99%
“…The vast array of receptors present in these granulocytes makes them very versatile cells, with a capacity to react to stimulus, co-stimulate cells in antigen presentation, and migrate to the tissues at physiological and pathological states [43]. Besides, this kind of cell is also equipped with certain intracellular receptors that regulate function (e.g., some toll-like receptors and the glucocorticoid receptor) likewise with a wide number of surface receptors [43][44][45].…”
Section: Figurementioning
confidence: 99%